EFFECT OF DIFFERENT PHOSPHORUS LEVELS AND SOWING DATES ON YIELD AND YIELD COMPONENT OF LABLAB (Lablab purpureus L. walp) VARIETIES IN RINGIM JIGAWA STATE, NIGERIA - Surajo, A.; Fagam, A. S.; Ali, G.; Sabo, M. U.; Bindawa, M. A.; Yahaya, S. U. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
Field experiment was conducted at the Jigawa State Horticultural Farm Ringim, during 2019, 2020 and 2021 wet seasons to investigate the effect of phosphorus levels and sowing date on the yield and yield components response of lablab varieties. The treatments consisted of four phosphorus levels (0, 20, 40 and 60 kg P/ha), three sowing dates (1st July, 15th July and 29th July) and two varieties of lablab (Dan Farankachi and Dan Inusa), which were factorially combined to give 24 treatments combination and laid out in a randomized complete block design (RCBD) replicated three times. Data were collected on number of root nodules per plant, number of days to physiological maturity and seed yield per hectare, and subjected to analysis of variance and Duncan’s Multiple Range Test (DMRT) was adopted in separating the means. The results showed that, application of 60 kg P/ha produced significantly higher yield characters of lablab. In terms of date of sowing, sowing lablab on 29th of July was found to be statistically (P ≤ 0.01) better in promoting yield of the crop than the other sowing dates. Variety Dan Inusa proved to be significantly (P ≤ 0.01) better than Dan Farankachi throughout the study period. Based on the result of this study, it could be concluded that application of 60 kg P/ha, Dan Inusa and sowing date of 29th July could be adopted by farmers for better yield of lablab in the study area, hence recommended for better yield.